Perfil metabólico de caprinos sob restrição alimentar e realimentação - Argolo, Erick Paiva de (Universidade Federal Rural do Semi-Árido, 2019)
The objective of this work was to evaluate the effects of dietary restriction and feedback on goat metabolic profile. In the experiment were used 25 castrated goats, separated in collective stalls. The experimental period was 114 days, comprised of a 30-day adaptation, where they received large and concentrated food, as well as free water, 42 days of food restriction and 42 days of feedback. The animals were divided into 5 groups of 5 (G1, G2, G3, G4 and G5) and submitted to isoprotein / hypoenergetic food restriction (40% - G1); isoenergetic / hypoprotein (20% - G2) isoprotein / hypoenergetic (20% - G3); isoenergetic / hypoproteic (40% - G4) and hypoproteic / hypoenergetic (30% - G5), later fed on hyperproteic and hyperenergetic diets. Blood samples were collected on days 0, 1, 3, 7, 14, 21, 28, 35 and 42 of restriction and 0, 7, 14, 21, 28, 35 and 42 of feedback. Hematological analysis included total red blood cell count, global leukocyte count, hematocrit and plasma proteins. For metabolic profile evaluation, the energetic variables analyzed were: glucose, cholesterol and triglycerides; whereas protein variables were: total protein, urea, albumin, creatinine, globulins, and enzymatic action metabolites creatine kinase (CK), aspartate transaminase (AST) and gamma glutamyltrasferase (GGT). During the restriction period, glucose showed no differences between treatments. However, a significant increase (p <0.05) was observed between times T0 and T1. Most of the values obtained for cholesterol remained within the reference values and only groups G3, G4 and G5 differed between times. Regarding triglycerides, there was a difference (p <0.05) between G4 and G5 in T7. In T42, groups G2 and G3 differed from each other, as did treatments G3 and G5. For the values of urea the groups G2 and G4 presented the lowest values among all, during the experiment. For total proteins, G5 treatment showed a decrease (p <0.05) in serum values after the 21st day of the experiment. The metabolic changes to which the animals underwent in this study were not sufficient to cause liver damage in them, according to AST, GGT values. In the feedback phase, even after the energy and protein level readjustment, there was no return to normal cholesterol levels in treatments G4 and G5. G2 and G5 presented means below the reference values for the glucose variable. At time T1, group G3 presented lower concentrations of urea. Albumin returned to normal values after 28 days, and remained so until the end. CK levels were normalized from T1, except for G4, whose normalization occurred at T7. Among the analyzed variables, glucose, total protein and albumin were not efficient to detect the proposed deficiencies in restrictive diets, while cholesterol, triglycerides, urea and globulins allowed the identification of short- and medium-term protein-energy deficiencies. . In some groups, the feedback promoted the reestablishment of the levels of some protein and energy metabolites. The groups maintained on hypoproteic or hypoproteic and hypoenergetic diets presented greater difficulties for such reestablishment.
Keywords: Perfil proteico; Perfil energético; Metabolismo; Desequilíbrio nutricional; Protein profile; Energy profile; Metabolism; Nutritional imbalance; CIENCIAS AGRARIAS::MEDICINA VETERINARIA